Observing the user experience a practitioner's guide to user research - Kuniavsky, Mike. (San Francisco, Calif. : Morgan Kaufmann Publishers, 2003)
The gap between who designers and developers imagine their users are, and who those users really are can be the biggest problem with product development. Observing the User Experience will help you bridge that gap to understand what your users want and need from your product, and whether they'll be able to use what you've created. Filled with real-world experience and a wealth of practical information, this book presents a complete toolbox of techniques to help designers and developers see through the eyes of their users. It provides in-depth coverage of 13 user experience research techniques
Typhoon : a fable -- Do a usability test now! -- Balancing needs through iterative development -- The user experience -- The research plan -- Universal tools : recruiting and interviewing -- User profiles -- Contextual inquiry, task analysis, card sorting -- Focus groups -- Usability tests -- Surveys -- Ongoing relationships -- Log files and customer support -- Competitive research -- Others' hard work : published information and consultants -- Emerging techniques -- Reports and presentations -- Creating a user-centered corporate culture.
Title from title screen.
Includes bibliographical references and index.
Title from website (viewed Jan. 20, 2006).
Keywords: Human-computer interaction; User interfaces (computer systems).; Electronic books